Effects of regulated deficit irrigation combined with optimized nitrogen fertilizer management on resource use efficiency and yield of sugar beet in arid regions. (20th December 2022) - Zhou, Hongliang; Xu, Pengjie; Zhang, Lijuan; Huang, Ruimin; Zhang, Chunyuan; Xiang, Dao; Yang, Mingfeng; Wang, Kaiyong; Dong, Xinjiu; Fan, Hua
Abstract: Regulated deficit irrigation (RDI) can suppress excess vegetative growth of crops and improve water use efficiency. However, the effects of RDI combined with split application of nitrogen (N) fertilizer on sugar beet in arid regions are not clear. Therefore, in Xinjiang, China (2019–2021), N fertilizer (0 kg N ha −1 (N0); 150 kg N ha −1 (N1); 225 kg N ha −1 (N2)) was applied before sowing and at the canopy rapid growth stage (CRGS) of sugar beet in three ratios (20%: 80% (T1); 30%: 70% (T2); 40%: 60% (T3)). Besides, RDI was also applied at the CRGS of sugar beet. Finally, the responses in water and N use efficiency, dry matter accumulation, and yield of sugar beet were analyzed. The results showed that the root yield, water use efficiency for root yield (WUEry), and water use efficiency for sugar yield (WUEsy) of sugar beet in the N2 treatments increased by 3.71%–11.80%, 8.17%–24.84%, and 9.47%–16.46%, respectively, but the agronomic N use efficiency (aNUE) reduced by 1.12%–24.91%, compared with those in the N1 treatments. Besides, compared to mode T3, mode T1 increased dry matter accumulation and yield by enhancing leaf gas exchange, and finally significantly increased aNUE, WUEry, and water use efficiency for sugar yield (WUEsy) by 48.54%–82.39%, 8.75%–24.58%, and 9.95%–35.71%, respectively. The results of 15 N isotope tracing showed that under RDI and N1 level, increasing the proportion of topdressed N could reduce the 15 N loss by 16.02% and increase the 15 N accumulated in plants by 19.31%. In conclusion, increasing the N topdressed at the CRGS combined with RDI could improve the water and N use efficiency and yield of drip-irrigated sugar beet in arid areas. Highlights: Nitrogen (N) fertilizer management increased water and N use efficiency of sugar beet. N fertilizer management increased sugar beet yield under regulated deficit irrigation. N fertilizer management coupled with regulated deficit irrigation reduced 15 N loss.